Migration Success Strategy and Implementation of Enterprise System: A Case Study on PT XYZ Biller Message Switching and Aggregator Service Merger Work From Home - Oristania Wahyu Nabasya (AI Society & STMIK Indonesia, 2024)
Purpose – The purpose of the research is to determine the strategy for the successful implementation of Biller Message Switching and Aggregator carried out by organizations with multicultural employees during work from home conditions. Methodology – The method used in this research was a summative evaluation with the research subjects of the merger of Bank X, Bank Y, and Bank Z. Research subjects were chosen because of the success of the development team in integrating enterprise systems to support the merger process carried out during the pandemic. Results – The results of the research concluded that the ES implementation strategy during the pandemic required consistency, actively documenting each process, over-communicating, and using the appropriate SDLC method. Originality – This research conducted a thematic analysis on the process of integrating and migrating ES companies that merged during the pandemic. Contribution – This research contributes to organizations that want to integrate and migrate ES during the pandemic. For academics, research can serve as a foundation for future research in developing theories of ES implementation in virtual or pandemic environments.